POLITIK HUKUM PIDANA DALAM UPAYA PENGHAPUSAN KEKERASAN RUMAH TANGGA SEBAGAI WUJUD PENGAKUAN DAN PERLINDUNGAN HAM - Nadir Nadir (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
Violence in household such as physical, psychological, sexualand economical violence is a form of criminal action happens inhousehold in which the doer and victim are from the samehousehold. The way of penal policy through the government insolution of violence in household is formed in norm codificationof positive law (positive wettelijk), by carrying out UU number 23of 2004 about abolition of violence in a household. Thisregulation is a form of government attention to human rights(HAM), and gender, non discrimination and the protection ofviolence victims in a household.